Effect of welding heat input on microstructure and properties of TC4 titanium alloy ultra-narrow gap welded joint by laser welding with filler wire. (6th January 2021) - Fang, Naiwen; Guo, Erjun; Huang, Ruisheng; Yin, Limeng; Chen, Yongsheng; Zeng, Caiyou; Cao, Hao; Zou, Jipeng; Xu, Kaixin
Abstract: A 10 mm narrow gap TC4 titanium alloy welded joint by laser welding with filler wire was obtained by different welding heat inputs. The microstructures of the welded joint were analyzed by OM, SEM, XRD and EBSD. The mechanical properties of the welded joint were analyzed by microhardness test and tensile test. The results show that with the increase of laser welding heat input, the average grain size and width of the equiaxed crystal zone in the center of the weld increases, the grain angle in the columnar crystal zone gradually tends to be perpendicular to the center of the weld, and the width of the heat affected zone (HAZ) increases without obvious grain coarsening. The HAZ of the welded joint is softened, and its microhardness value is lower than that of the weld and the base metal. The tensile strength of the welded joint is slightly higher than those of the base metal, but the elongation after fracture is less than that of the base metal, and it decreases with the increase of laser welding heat input.